Tc17/IL-17A Up-Regulated the Expression of MMP-9 via NF-κB Pathway in Nasal Epithelial Cells of Patients With Chronic Rhinosinusitis - Chen, Xiaohong; Chang, Lihong; Li, Xia; Huang, Jiancong; Yang, Luoying; Lai, Xiaoping; Huang, Zizhen; Wang, Zhiyuan; Wu, Xifu; Zhao, Jun; Bellanti, Joseph A.; Zheng, Song Guo; et al. (Frontiers in Immunology, 2018)
Chronic rhinosinusitis (CRS) is a common chronic inflammatory disease of the upper airways involving nasal cavity and sinus. Deriving both from its clinical complexity with protean clinical manifestations as well its pathogenetic heterogeneity, the molecular mechanisms contributing to the pathogenesis of CRS remain unclear, and attract a wide interest in the field. Current evidences indicate that IL-17A is highly expressed in chronic rhinosinusitis with nasal polyps (CRSwNP). However, its pathogenetic role in regulation of tissue remodeling of CRSwNP remains unknown. The present study aimed to investigate the cellular origins and functions of IL-17A cytokine in CRSwNP, and further determined whether IL-17A could affect the expression of metalloproteinases (MMPs), the remodeling factors of CRSwNP. The results showed that the expression of IL-17A was upregulated in nasal tissues of patients with CRSwNP compared to those with chronic rhinosinusitis without nasal polyps (CRSsNP) and controls. CD8+ cytotoxic T lymphocytes (Tc) were major IL-17A producers in nasal tissues of CRSwNP. Interleukin (IL)-17-producing CD8+ T cells (Tc17) was significantly higher in nasal tissues of CRSwNP than CRSsNP and controls. Nonetheless, no difference was observed among the IL-17A in peripheral blood lymphocytes of these three groups. Moreover, in the same patients, IL-17A expression was negligible in lymphocytes of peripheral blood when compared with nasal tissues. Increased gene and protein expression of MMP-7 and MMP-9 in patients with CRSwNP compared with controls were observed. In CRSwNP samples, IL-17A receptor (IL-17AR) co-localized with MMP-9 and they were mainly expressed in the epithelial cells. MMP-9 expression was up-regulated both in Primary human nasal epithelial cells (PHNECs) and a nasal epithelial cell line (RPMI 2650) by IL-17A treatment, and diminished by anti-IL-17AR treatment. Furthermore, IL-17A promoted the expression of MMP-9 by activating the NF-κB signal pathway. Thus, our results have revealed a crucial role of IL-17A and Tc cells on pathogenesis and tissue remodeling of CRSwNP.